Early Immunologic Events at the Tick-Host Interface - Heinze, Dar M. (Public Library of Science, 2012)
Ixodes species ticks are competent vectors of tick-borne viruses including tick-borne encephalitis and Powassan encephalitis. Tick saliva has been shown to facilitate and enhance viral infection. This likely occurs by saliva-mediated modulation of host responses into patterns favorable for viral infection and dissemination. Because of the rapid kinetics of tick-borne viral transmission, this modulation must occur as early as tick attachment and initiation of feeding. In this study, cutaneous bite-site lesions were analyzed using Affymetrix mouse genome 430A 2.0 arrays and histopathology at 1, 3, 6, and 12 hours after uninfected Ixodes scapularis nymphal tick attachment. At 1 and 3 hrs after attachment, the gene expression profile is markedly different than at later time points. Upregulated gene ontology term clusters enriched at 1 and 3 hrs were related to post-translational modification. At 6 and 12 hrs, cytoskeletal rearrangements, DNA replication/cell division, inflammation, and chemotaxis were prominent clusters. At 6 and 12 hrs, extracellular matrix, signaling, and DNA binding clusters were downregulated. Histopathological analysis shows minimal inflammation at 1 and 3 hrs but an appreciable neutrophil infiltrate at 6 and 12 hrs. In addition, putative hyperemia, localized necrosis, and increased ECM deposition were identified. Putting the gene expression and histopathology analysis together suggests early tick feeding is characterized by modulation of host responses in resident cells that merges into a nascent, neutrophil-driven immune response by 12 hrs post-attachment.